Analisis Finansial dan Sensitivitas Usaha Kecil Menengah Dodol Coklat - Nurainy, Fibra; Nawansih, Otik; Sitanggang, Merry Monika (Politeknik Negeri Lampung., 2015)
This research was purposed to determine financial aspects of chocolate dodol home industry. The result of investment feasibility are reasonable to continue (NPV>0, Net B/C >1,IRR> 22% discount rate and raw?s material (cocoa beans) as many as 10%-50% and the fuel as many as 15%-90 PP< 5 years of economical?s age. The result of sensitivity variable cost increase likes % still reasonable to continue (NPV>0, Net B/C >1,IRR> 22% discount rate and PP< 5 years of economical?s age). Keywords: Chocolate dodol, Financial Analysis, Sensitivity.